2016
DOI: 10.1038/ijo.2016.40
|View full text |Cite
|
Sign up to set email alerts
|

Is obesity becoming the new normal? Age, gender and racial/ethnic differences in parental misperception of obesity as being ‘About the Right Weight’

Abstract: Significant age differences in the odds for parental misclassification of obesity as 'about the right weight' were detected in female children, but not males. Hispanic males with obesity were significantly less likely to be misperceived as being 'about the right weight' when compared with their non-Hispanic White peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 21 publications
2
24
0
2
Order By: Relevance
“…In addition, we found that mothers of daughters more accurately classified their child's weight compared with mothers of sons. The keen awareness of their female children's weight in the current study matches prior research that mothers of daughters are more likely to accurately estimate their child's weight status than mothers of sons (Maynard et al, 2003;Twarog, Politis, Woods, Daniel, & Sonneville, 2016 In addition to the results being fairly consistent to previous studies, the current study contributes to the literature by evaluating factors that predict maternal concerns for her child's future weight status. Our findings indicate that mothers with a higher BMI were concerned that their child would become overweight in the future.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, we found that mothers of daughters more accurately classified their child's weight compared with mothers of sons. The keen awareness of their female children's weight in the current study matches prior research that mothers of daughters are more likely to accurately estimate their child's weight status than mothers of sons (Maynard et al, 2003;Twarog, Politis, Woods, Daniel, & Sonneville, 2016 In addition to the results being fairly consistent to previous studies, the current study contributes to the literature by evaluating factors that predict maternal concerns for her child's future weight status. Our findings indicate that mothers with a higher BMI were concerned that their child would become overweight in the future.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, we found that mothers of daughters more accurately classified their child's weight compared with mothers of sons. The keen awareness of their female children's weight in the current study matches prior research that mothers of daughters are more likely to accurately estimate their child's weight status than mothers of sons (Maynard et al., ; Twarog, Politis, Woods, Daniel, & Sonneville, ). This consistent finding is problematic because if mothers of male children are unaware and unconcerned about their son's weight, they may be less likely to accept obesity reduction information from healthcare providers, such as school nurses.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Obesity was significantly less likely to be misperceived among girls 11 to 15 years of age than among girls 6 to 10 years of age (OR, 0.46; 95% CI, 0.29–0.74; P =0.002) and among Hispanic males than among white males (OR, 0.58; 95% CI, 0.36–0.93, P =0.02). 85 Notification of a child’s unhealthy weight by healthcare practitioners increased from 22% in 1999 to 34% in 2014. 86 …”
Section: Overweight and Obesitymentioning
confidence: 99%
“…Obesity may increase the risk of many health problems, including type 2 diabetes (T2D), cardiovascular disease, metabolic syndrome (MS), certain cancers and mortality , and is considered to result from the interaction between environmental factors and genetic components. Indeed, striking racial differences exist in the incidence and prevalence of obesity , supporting the possible contribution of hereditary components to the onset of obesity. However, the exact obesity‐related gene network and underlying molecular mechanisms are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%